The Probiotic Lactobacillus rhamnosus for Alleviation of Helicobacter pylori-Associated Gastric Pathology in East Africa - Westerik, Nieke; Reid, Gregor; Sybesma, Wilbert; Kort, Remco (Frontiers in Microbiology, 2018)
.The probiotic Lactobacillus rhamnosus GG can play a role in establishing a harmless relationship with Helicobacter pylori and reduce gastric pathology in East African populations. Helicobacter pylori has the ability to inhabit the surface of the mucous layer of the human stomach and duodenum. In the developing world, an estimated 51% of the population is carrier of H. pylori, while in some Western countries these numbers dropped below 20%, which is probably associated with improved sanitation and smaller family sizes. Colonization by H. pylori can be followed by inflammation of the gastric mucus layer, and is a risk factor in the development of atrophic gastritis, peptic ulcers and gastric cancer. Notwithstanding the higher prevalence of H. pylori carriers in developing countries, no equal overall increase in gastric pathology is found. This has been attributed to a less pro-inflammatory immune response to H. pylori in African compared to Caucasian populations. In addition, a relatively low exposure to other risk factors in certain African populations may play a role, including the use of non-steroidal anti-inflammatory drugs, smoking, and diets without certain protective factors. A novel approach to the reduction of H. pylori associated gastric pathology is found in the administration of the probiotic bacterium Lactobacillus rhamnosus yoba 2012, the generic variant of Lactobacillus rhamnosus GG. This gastro-intestinal isolate inhibits H. pylori by competition for substrate and binding sites as well as production of antimicrobial compounds such as lactic acid. In addition, it attenuates the host’s H. pylori-induced apoptosis and inflammation responses and stimulates angiogenesis in the gastric and duodenal epithelium. The probiotic Lactobacillus rhamnosus yoba 2012 is not able to eradicate Helicobacter pylori completely, but its co-supplementation in antibiotic eradication therapy has been shown to relieve side effects of this therapy. In Uganda, unlike other African countries, gastric pathology is relatively common, presumably resulting from the lack of dietary protective factors in the traditional diet. Supplementation with Lactobacillus rhamnosus yoba 2012 through local production of probiotic yoghurt, could be a solution to establish a harmless relationship with Helicobacter pylori and reduce gastric pathology and subsequent eradication therapy treatment.